Study on the Equivalent Permeability Coefficient of Karst Conduit with Single Conduit and Multigroup Fissures. (23rd June 2022) - Li, Tianyu; Fan, Qiuyan; Yang, Pengshuai; Liang, Jiahui
Abstract : In order to improve the calculation method of the conversion coefficient of karst conduit under the condition of multiple fissures and conduit intersecting, the indoor test model of karst groundwater seepage with a single conduit and multiple groups of fissures is established. Under the condition of fixed upstream and downstream water heads, the changes of karst conduit water head under different fissures width, fissures combination, and different flow velocity were observed. The test found that the karst conduit water level gradually decreased with the increase of distance, showing an obvious linear relationship. Based on the above-observed water head law, the conversion coefficient of fissures influence is introduced into the Darcy–Weisbach formula, and the regression analysis of test data are used to obtain the calculation formula of the equivalent permeability coefficient of conduit intersecting multiple fissures and karst conduit. The formula is applicable to the case that the fissures are equidistant and the conduit is vertical and does not change dramatically along the conduit.